Perancangan Mesin Analisa Potongan Pellet Otomatis Menggunakan Software Blender Dengan Metode MDLC - Muhammad Yafi D; Rusindiyanto Rusindiyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
PT XYZ) is a company which focuses on integrated aquaculture. Operating since 1987, PT XYZ has a fish and shrimp feed factory, fish and shrimp breeding and rearing as well as marine fish food processing and cold storage for local and global markets. At PT XYZ, especially the Quality Control division, there are still ineffective analysis activities, namely piece length analysis. An effort to increase productivity is by designing an automatic cut length analysis machine with the aim of maximizing efficiency and effectiveness. Therefore, the objective function of this research was carried out to design and increase productivity and reduce inefficient activities. From this, it is necessary to design and optimize activities to have a positive impact on the company. This research uses Blender software and the Multimedia Development Life Cycle (MDLC) method which includes concept, design, material collecting, assembly, testing and distribution. The results of this research show that this machine design is very effective and practical for the company and allows the company to improve maximum performance